Вот подробный ответ на фото
Ответ:
Пошаговое объяснение:
№ 1
2(а - 3)² + 2а(3 + а) =
2(а² - 6а + 9) + 2а(3 + а) =
2а² - 12а + 18 + 6а + 2а² =
4а² - 6а + 18
№ 2
3(6 - 2с)² + 3(b + c)(6 + 2c) =
3(36 - 24c + 4c²) + 3(6b + 2bc + 6c + 2c²) =
(108 - 72c + 12c²) + (18b + 6bc + 18c + 6c²) =
108 - 72c + 12c² + 18b + 6bc + 18c + 6c² =
18c² - 54c + 18b + 6bc + 108
№3
(3 + 2y)(x - 5) - 2(1 + y) =
(3x - 15 + 2xy - 10y) - 2 - 2y =
3x - 15 + 2xy - 10y - 2 - 2y =
3x + 2xy - 12y - 17
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Verified answer
Вот подробный ответ на фото
Ответ:
Пошаговое объяснение:
№ 1
2(а - 3)² + 2а(3 + а) =
2(а² - 6а + 9) + 2а(3 + а) =
2а² - 12а + 18 + 6а + 2а² =
4а² - 6а + 18
№ 2
3(6 - 2с)² + 3(b + c)(6 + 2c) =
3(36 - 24c + 4c²) + 3(6b + 2bc + 6c + 2c²) =
(108 - 72c + 12c²) + (18b + 6bc + 18c + 6c²) =
108 - 72c + 12c² + 18b + 6bc + 18c + 6c² =
18c² - 54c + 18b + 6bc + 108
№3
(3 + 2y)(x - 5) - 2(1 + y) =
(3x - 15 + 2xy - 10y) - 2 - 2y =
3x - 15 + 2xy - 10y - 2 - 2y =
3x + 2xy - 12y - 17